Effects Of Using Multisensory Approach In The Mastery Of English Language Skills Among Students With Intellectual Disability In The State Of Kuwait - Moustafa, Amr Mahmoud (2019)
The purpose of this study is to determine the impact of using the multisensory approach in mastering English language skills among students with mild intellectual disability (MID) in the state of Kuwait and to investigate the perceptions of special education teachers towards teaching literacy skills to students with MID. The study adopted both quantitative and qualitative methods to collect the date. An ABA model was used to collect the quantitative data and the results were analyzed using visual analysis, time series and intro observer agreement. Thematic analysis was conducted to analyse the data obtained from a semi-structured interview with special needs teachers in bilingual schools. The study sample comprised three students with MID who participated in six-week literacy programs in a special needs centre in Kuwait and six special education teachers in special needs bilingual schools in Kuwait. Results showed that the multi-sensory approach was effective in teaching English letter identification, letter–sound correspondence and reading consonant–vowel–consonant words to students. Thematic analysis of qualitative data revealed three themes from the conducted interview. The research also showed that special needs teachers in bilingual schools lack resources, proper curricula and professional training in literacy to deliver proper and effective programs in teaching literacy to students with MID. Schools must pay serious attention to the importance of teaching literacy skills to students and providing teachers with all the possible tools to teach suchskills.